Effect of sterility value on qualities of Chinese braised culled steer beef in retort pouch - Kumueang, C.; Tangwatcharin, P.; Sorapukdee, S. (International Journal of Agricultural Technology, 2020)
The results showed that their cook values were 72.42, 87.05 and 95.04 min, respectively. Microbiological analysis and sterility test were proved that the samples were safety for microbiological quality. However, parameters of texture profile (hardness, gumminess, springiness and chewiness) decreased as F0 value was increased (p<0.05). Similarly, shear force decreased with increasing F0 value (p<0.05). The CIE L* value increased and CIE a* values decreased as F0 value was increased. For sensory evaluation, semi-trained panelists mostly impressed this product which produced by F0 value of 10 min (p<0.05). Therefore, the development of Chinese braised beef in retort pouch was satisfied with F0 value of 10 min.